2014
DOI: 10.1371/journal.pone.0110692
|View full text |Cite
|
Sign up to set email alerts
|

Allele Frequencies of Variants in Ultra Conserved Elements Identify Selective Pressure on Transcription Factor Binding

Abstract: Ultra-conserved genes or elements (UCGs/UCEs) in the human genome are extreme examples of conservation. We characterized natural variations in 2884 UCEs and UCGs in two distinct populations; Singaporean Chinese (n = 280) and Italian (n = 501) by using a pooled sample, targeted capture, sequencing approach. We identify, with high confidence, in these regions the abundance of rare SNVs (MAF<0.5%) of which 75% is not present in dbSNP137. UCEs association studies for complex human traits can use this information t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…Remarkably, our results indeed show that a vast majority of UCE polymorphisms exhibit extremely low MAFs-less than 6% occur at a frequency of >1%. Depletion of prevalent polymorphisms from UCEs has also been confirmed by Silla et al (2014). It may be assumed that recurrent polymorphisms are less likely associated with fitness, while those occurring at lower MAFs more likely have deleterious consequences.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Remarkably, our results indeed show that a vast majority of UCE polymorphisms exhibit extremely low MAFs-less than 6% occur at a frequency of >1%. Depletion of prevalent polymorphisms from UCEs has also been confirmed by Silla et al (2014). It may be assumed that recurrent polymorphisms are less likely associated with fitness, while those occurring at lower MAFs more likely have deleterious consequences.…”
Section: Discussionmentioning
confidence: 89%
“…At present, UCEs are among the most popular DNA markers for phylogenomic analysis (Tagliacollo and Lanfear, 2018). They might also be good candidates for targeted sequencing projects and association studies (Silla et al, 2014) and might present valuable and easily detectable disease biomarkers. Bao et al (2016) for example found association between rs8004379 and prostate cancer-specific mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is unclear whether overlapping binding sites would be sufficient to explain extreme non-coding conservation, given promiscuity of binding sites and binding site divergence between species ( 76 ). A recent paper also proposed that CNEs are not under selective pressure as a whole DNA segment but are under various evolutionary constraints on the single nucleotide level ( 77 ), suggesting that overlapping TFBS likely do not account for the degree of conservation characteristic of CNEs.…”
Section: General Features Of Non-coding Conservationmentioning
confidence: 99%
“…This view explains the gradual increase of the δ-distance of a series of CNE collections from their surrogate sequences, when these CNE datasets are produced by gradual increase of the conservation thresholds (see Table 2). Moreover, the high performance of GGSs in distinguishing among all examined CNE classes, for all considered lengths n , does not support the suggestion that the selective pressure shaping CNEs, and especially the more extremely conserved ones (mentioned as Ultra-Conserved Elements or UCEs in that work), is exerted on the single nucleotide level 37 , since GGSs capture nucleotide correlations extending along whole stretches of DNA.…”
Section: Resultsmentioning
confidence: 77%